PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR KOMPETENSI PENGETAHUAN SISWA KELAS IV SD MUHAMMADIYAH SUNGAI APIT - Lusi Hardianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
The success full implementation of the 2013’s curriculum in superior learning activities in primary schools is determined by the role of the teacher. The goals from this research are to study the improvement of student learning outcomes before and after with the problem-based learning model. Classroom Action Research was employed in this study with descriptive analysis, conducted in 2 cycles. 17 students of the 4th grade of SD Muhammadiyah Sungai Apit were involved as participants. The tools used to collect data in this study are observation sheets and tests of knowledge competency learning outcomes. Based or the results of the research obtained from increasing the scores of teacher and student activities. In the first cycle, teacher activity increased from 75% to 90% and in the second cycle changed the rate from 90% to 95%. While student activity increased from 70% to 85% of the second cycle of 85% of 95%. The average score of student learning outcomes also increased, in the first cycle increased by 12.50% and the second cycle increased again to 30.29% after approval of the action. The problem-based learning model is also increased. participants and able to make good cooperation between teachers with students and students with other students. This concludes that the problem-based learning model can improve the competency learning outcomes of 4th-grade students at SD Muhammadiyah Sungai Apit.